INPUT, PROCESS AND OUTPUT SYSTEM THEORY APPROACH IN EDUCATIONAL INSTITUTIONS - Firman Sidik (Irfani (e-Journal), 2022)
This study aims to look at the theoretical approach of input, process and output systems in educational institutions, as an effort to see the quality of educational institutions which are the locomotive in producing a quality generation. The method used in this research is literature review. The results show that the education system is a unit whose parts work together to achieve the expected results based on predetermined needs. Every system must have a purpose, and all activities of all components or parts of it are directed to achieve that goal. Therefore, with the input-process-output education system theory, it is hoped that all educational activities will be more systematic and of higher quality.